High temperature oxidation resistance of metal silicide incorporated ZrB2 composite coatings prepared by vacuum plasma spray. Issue 10 (December 2015) - Wang, Zhong; Niu, Yaran; Hu, Cui; Li, Hong; Zeng, Yi; Zheng, Xuebin; Ren, Musu; Sun, Jinliang
Abstract: Metal silicides are often utilized to enhance high temperature oxidation resistance for refractory ZrB2 ceramics or coatings owing to the capability to form glassy silica layer. However, the role of metal elements in silicides on maintaining the glassy layer needs to be elucidated. In the present study, TaSi2 and MoSi2 incorporated ZrB2 composite coatings were respectively prepared by vacuum plasma spray (VPS) technology and their oxidation behaviors were comparatively investigated. The oxidation tests carried out in ambient air at 1773 K confirmed the crucial function of glassy silica layer on high temperature oxidation resistance for both of the metal silicide incorporated ZrB2 coatings. More importantly, the metal elements in silicide additives were revealed to have great influence on the integrity of glassy silica layer. The oxidation of element Ta in TaSi2 generated plate-like compound TaZr2.75 O8, which impaired the consistency and completeness of silica layer, creating opportunity for oxygen diffusion. However, MoB, the oxidation product of element Mo in MoSi2, could help supporting the integrity of silica layer. MoB played the role defending the wholeness of silica layer and reducing the evaporation of B2 O3 and MoO3 at the same time. Better oxidation resistance of ZrB2 –MoSi2 composite coating was found as compared with ZrB2 –TaSi2 composite coating.